Penguatan Usaha Kuliner Ikan dalam Mendukung Aktivitas di Kampung Lauk Bubulak Kota Bogor - Batubara, Rima Pratiwi; Sari, Dhanik Puspita; Setiawan, Aditya Sugih (Jurnal Pemberdayaan Masyarakat, 2024)
Kampung Lauk Bubulak is one of the villages in Bogor City. Kampung Lauk Bubulak is a tough village that utilizes the water flow in the ditch by growing fish such as catfish (lele), catfish (patin) and goldfish. Community service is carried out to strengthen the fish culinary business in supporting activities in Kampung Lauk Bubulak Bogor. Implementation takes the form of socialization and training regarding the manufacture of fish-based products. The methods used refer to training, continuing education, increasing understanding and consultation. The results of the activities obtained include providing material related to hygiene in food products and training regarding the manufacture of fish-based food products. Discussion activities were also carried out regarding the results of independent implementation by the community. Discussions regarding the fixation of material use, production flow, marketing flow and the division of work in society. In the final stage, the type of packaging that is suitable for the product that has been produced is also determined. The type of packaging used is boilpack. This boilpack material of course has several advantages for packaging processed fish, including freezer cold resistance and vacuum sealing, suitable for the saoce vide technique cooking method, more practice, and a more professional appearance.